Science and the Qur'an - Al-Mehrab (Kuala Lumpur : Al-Mehrab)
Science is all about Allah S.W.T. and Allah's Creation. The study of science should lead one to a better understanding of the Creator and His Creation. Therefore, the study of science should lead one to increased imaan and a deeper submission to Allah's will.
Keywords: Qur'an and science; Islam and science